Zero-echo time imaging achieves whole brain activity mapping without ventral signal loss in mice - Ayako Imamura; Rikita Araki; Yukari Takahashi; Koichi Miyatake; Fusao Kato; Sakiko Honjoh; Tomokazu Tsurugizawa (NeuroImage)
Functional MRI (fMRI) is an important tool for investigating functional networks. However, the widely used fMRI with T2*-weighted imaging in rodents has the problem of signal lack in the lateral ventral area of forebrain including the amygdala, which is essential for not only emotion but also noxious pain. Here, we scouted the zero-echo time (ZTE) sequence, which is robust to magnetic susceptibility and motion-derived artifacts, to image activation in the whole brain including the amygdala following the noxious stimulation to the hind paw. ZTE exhibited higher temporal signal-to-noise ratios than conventional fMRI sequences. Electrical sensory stimulation of the hind paw evoked ZTE signal increase in the primary somatosensory cortex. Formalin injection into the hind paw evoked early and latent change of ZTE signals throughout the whole brain including the subregions of amygdala. Furthermore, resting-state fMRI using ZTE demonstrated the functional connectivity, including that of the amygdala. These results indicate the feasibility of ZTE for whole brain fMRI including the amygdala and we first show acute and latent activity in different subnuclei of the amygdala complex after nociceptive stimulation.